A queda do céu como uma autobiografia menor - Fernandes, Francisco Felipe Paiva (2016)
"The Falling Sky like an Autobiography minor" (A queda do céu como uma autobiografia menor) aims to achieve a theoretical analysis of the work The Fall from the Sky (2015) of Davi Kopenawa and Bruce Albert. In a specific way we chose to oppose the canon theory that deals with the records of the myself to the text above, aiming to propose new concepts that support a renewed interpretation of this scripture. In such a way, the problems pointed out in the course of the analysis showed the limits that heuristic the own theories supporting when encountered with the textuality that, at least in our hypothesis, not favoring a fruitful and valuable for the interpretation of The Fall from the Sky. In the face of such finding, we emphasize the methodology that follows: We conducted a foucaultian archeology of theories by determining, with this, the conditions of possibility of the emergence of these knowledges, as partial result achieved a diagnosis around the main problems epistemic as well as of the most important lines of understanding that the epistemes feature. Subsequently, we propose new forms of interpretation as well as new approaches around The Fall from the Sky. Our result is to renew the concept of real and representational that guide much of literary theory, as well as a new way to understand the role of narrator in autobiographical narratives. Thus, for the theoretical basis of this study were used the authors of guidelines as Michel Foucault (2008), Jacques Derrida (1999), Judith Butler (2015), Philip Lejuene (2018), Paul De Man (1886), Leonor Arfuch (2010), Jacques Lacan (1999), Roy Wagner (2010), Eduardo Viveiros de Castro (2015) and Deleuze & Guattari (2014).